Implementasi pembelajaran Pendidikan Agama Islam dan pembelajaran Karakter dalam menanamkan Karakter Religius pada peserta didik - Kartika, Adhisti Malla (Maliki Interdisciplinary Journal, 2024)
The purpose of this article is to describe the application of Islamic religious and character education in shaping the religious character of students in various schools. Islamic religious teachings are an effort to bring about changes in attitudes and behavior that are in line with Islamic teachings. The research method used is qualitative which includes explanations of various library research sources as the main data source, as well as other sources related to religious character education books. The results of the research show that the application of Islamic religious education and moral education includes: 1. Application of Islamic religious education and moral education in presenting students’ religious character, namely. planning, implementing and evaluating education. 2. Supporting factors, namely school facilities and infrastructure, teacher enthusiasm in teaching, clean and comfortable environment, school activity program including activities inside and outside the school. 3. Preventive factors: lack of students’ internal motivation, influence of students’ family factors, influence of friendships, influence of cellphone use and lack of teacher role models. 4. Solution: understanding and comprehending student psychology, holding parent training and meetings, advising students in choosing good friends, involving student parents in student social leadership, optimizing social media, pushing the limits of smartphone use. Students can provide good role models and a culture that reminds each other of goodness.